A Comparative Study of Liquid Nitrogen Cryotherapy as Monotherapy versus in Combination with Podophyllin in the Treatment of Condyloma Acuminata - صالح حسن (Latakia University Journal -Medical Sciences Series, 2020)
Condyloma Acuminata (CA) is a common viral sexually transmitted disease. Although various treatment modalities are available for treating CA, but none of them can achieve 100% response rate. In a search for better response rate and less recurrence rate, the combination of cytotoxic agent Podophyllin with ablative liquid nitrogen cryotherapy was evaluated over cryotherapy alone. Sixty patients with multiple CA were randomly assigned to two groups in the study. Thirty patients in group A received double freeze thaw cycle of 25 seconds of liquid nitrogen cryotherapy. Thirty patients in Group B were subjected to liquid nitrogen cryotherapy in a similar manner followed by application of not more than 0.5 ml of 25% Podophyllin solution. The complete response rate and the recurrence rate in the Group B in our study were comparable to Group A as the difference was statistically insignificant. But the differentiating point was that the similar results were obtained in Group B with an average 1.2 sessions per patient in comparison to an average of 1.67 sessions per patient in Group A. Cryotherapy represents a simple, safe and effective regimen for the treatment of multiple CA which in combination with Podophyllin is even more effective as a single session procedure; thereby shortening the treatment regimen.